The effect of economic transformation programme on the accounting information systems of an agricultural company: an organisational change perspective / Kamaruzzaman Muhammad ... [et al.] - Muhammad, Kamaruzzaman; Mastuki, Nor’Azam; Darus, Faizah (2014)
Organisational change arises when an organisation has undergone a transformation in its operational structure and activities which are departure from the norm as a result of new external and internal forces. This paper presents the findings of an investigation on an organisational change within a group of agriculture companies (the Group) following the implementation of Economic Transformation Programme by the Malaysian government. Using content analyses and structured interviews, this study found that following ETP, the Group has since transformed its business model and corporate structure. The business model has changed from being a developer of commercial plantations to a globally integrated and diversified agriculture business. The Group’s organisational structure has been rearranged and reclassified into six business clusters to reflect its main business activities. The six business clusters are palm upstream, palm downstream, research and development and agriculture service, rubber, sugar and, transport, logistics and marketing. In accommodating the requirements of the new business model and corporate structure, the accounting information systems have experienced a major transformation of which new system has been developed and existing system has been upgraded and integrated with the new system. The findings in this study provide some understanding on the effect of government policy on the accounting information systems of the group and subsequently provide guidelines to other companies of the same nature on the issues and the strategies to overcome such issues.